Pengaruh Harga, Distribusi, dan Promosi terhadap Keputusan Pembelian Apparel Sepak Bola Lokal di Kota Makassar - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to determine: 1) the influence of price, distribution, and promotion on the purchasing decision of local football apparel products in Makassar City; 2) the influence of price on purchasing decision; 3) the influence of distribution on purchasing decision; and 4) the influence of promotion on purchasing decision. This research employs an associative method with a quantitative approach. The variables analysed include price, distribution, and promotion as independent variables, and purchasing decision as the dependent variable. The sample consisted of 100 respondents selected using a purposive sampling technique. Primary data were collected through questionnaires distributed to consumers who had purchased local football apparel. The data were analysed using multiple linear regression with the assistance of SPSS software. The results indicate that: 1) price, distribution, and promotion simultaneously have a significant effect on purchasing decisions; 2) price has a significant effect on purchasing decisions; 3) distribution has a significant effect on purchasing decisions; and 4) promotion has a significant effect on purchasing decisions.